MAKNA DIRI WANITA OBESITAS DI UNIVERSITAS RIAU - Aurora Agustin; Genny Gustina Sari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Obesity is a condition where body fat is in an excessive amount of condition.Being overweight is a scary thing for some individuals,besides being harmful to health it also makes a person unattractive from a physical point of view. Being over weight will cause a buildup of fat in the body that is very high if the condition occurs in a long period of time,there will be things are very contradictory. People who are obese tend to be more sensitive in interacting with people who are not obese. Obese women certainly have their own meaning on the body. The purpose of this study is to find out the meaning of obese women.This study uses qualitative research methods using symbolic interaction theory. The informants in this study were 4 female students from the University of riau who had an obese body chosen purposively. Data colection techniques used are through in-depth interviews, observation and documentation.The self-meaning of obese women at Riau University is teasing,disliked by the opposite sex, troublesome,discriminatory,eating, less nimble, lazy, not fashionable, unhealthy, and fat. This is in accordance with the theory of symbolik interaction where obese women make the body of obesity as an object so that the object will interact and bring meaning.